Konsep Jiwa dan Pengaruhnya dalam Kepribadian Manusia (Studi atas Tafsi>r al-Mishba>h Karya Quraish Shihab)
This article attempts to explore Qur’anic notion on soul and its influence on human personality as Quraish Shihab constructed in his Tafsi>r al-Mishba>h. Using psychological and semantical approaches, it parallelizes psychological with Qur’anic perspectives on the concept of soul. Then, it examines how the soul influences human personality. This paper concludes the following. First, Quraish Shihab’s view of the concept of soul can be understood by explaining his thought on the basic concept of human, psychical structure, and human behavioral motivation. Quraish Shihab said that humans’ basic character is kindness. The psychical structure consists of al-fit